Gymnotic uptake of AntimiRs alter microRNA-34a levels in 2D and 3D epithelial cell culture - Julie Weidner; Ewa Kolosionek; Reetta Holmila; Elisabeth Ax; Marion Garreau; Felix Gnerlich; Henric Olsson; Werngard Czechtizky; Stefan Vollmer; Anna M. Rydzik (Elsevier, 2023)
MicroRNAs are attractive therapeutic targets in many diseases, including chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis. Among microRNA inhibitors antimiRs have been proven successful in lowering aberrant microRNA levels in the clinic. We present a set of antimiRs targeting miR-34a, which has been shown to be dysregulated in chronic lung diseases. The tool compounds were taken up by a bronchial epithelial cell line and primary human bronchial epithelial cells, followed by efficient knockdown of miR-34a. Similar results were observed in 3D differentiated primary human bronchial epithelial cells cultured at the air-liquid interface. Varying chemical properties of antimiRs had significant impact on cellular uptake and potency, resulting in effective tool compounds for use in lung-relevant cellular systems. This report demonstrates gymnotic antimiR uptake and activity in 3D epithelial cell culture after apical administration, mimicking inhalation conditions.